2012
DOI: 10.1002/ange.201202451
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Cyclopropanes That Contain Fluorinated Tertiary Stereogenic Carbon Centers: A Chiral α‐Fluoro Carbanion Strategy

Abstract: Keywords: asymmetric synthesis · chiral fluoroalkylation reagent · cyclopropanation · fluorine · sulfoximine Scheme 4. Preparation of cyclopropanes 6 a and 6 b, which contain fluorinated quaternary stereogenic carbon centers.Scheme 5. Synthetic applications of product 4 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Firstly, we developed an efficient synthesis of ( R )‐ N ‐ tert ‐butyldimethylsilyl‐ S ‐fluoromethyl‐ S ‐phenylsulfoximine ( 1 ). ( R )‐ N ‐tosyl‐ S ‐fluoromethyl‐ S ‐phenylsulfoximine ( 3 ) was readily prepared according to reported procedures 10b. The tosyl group of 3 was readily removed in aqueous H 2 SO 4 (18.4 m) , thus affording ( R )‐S‐fluoromethyl‐S‐phenylsulfoximine ( 4 ) in 97 % yield.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, we developed an efficient synthesis of ( R )‐ N ‐ tert ‐butyldimethylsilyl‐ S ‐fluoromethyl‐ S ‐phenylsulfoximine ( 1 ). ( R )‐ N ‐tosyl‐ S ‐fluoromethyl‐ S ‐phenylsulfoximine ( 3 ) was readily prepared according to reported procedures 10b. The tosyl group of 3 was readily removed in aqueous H 2 SO 4 (18.4 m) , thus affording ( R )‐S‐fluoromethyl‐S‐phenylsulfoximine ( 4 ) in 97 % yield.…”
Section: Methodsmentioning
confidence: 99%
“…[53] Thus, the authors turned their attention to the charge-neutral sulfoximine-based CH 2 F reagent 3 h, originally developed by Hu and co-workers. [54] Reduction of the reagent requires strong reducing power (E red = À 2.02 V) because of its low electrophilicity. However, the authors developed a highly reducing organic photocatalyst, BDN (1,4-bis(diphenylamino)naphthalene) (E* ox = À 1.99 V).…”
Section: Use Of Ch 2 Fà Sulfoximine Reagentmentioning
confidence: 99%
“…In 2019, Koike and Akita reported that use of 3 e was unsuitable for photocatalytic monofluoromethylation because the 1e‐reduction generates a mixture of CH 2 F and aryl radicals (Scheme a) . Thus, the authors turned their attention to the charge‐neutral sulfoximine‐based CH 2 F reagent 3 h , originally developed by Hu and co‐workers . Reduction of the reagent requires strong reducing power ( E red =−2.02 V) because of its low electrophilicity.…”
Section: Strategies For Reductive Generation Of Fluoromethyl Radicalsmentioning
confidence: 99%
“…Fluoromethylation has recently been investigated, offering a single attachment point for the target substrate . However, fluoromethylene group transfer formally offers two connection points, giving access to monofluorinated 3-membered rings . Along this line, we have recently reported on fluoromethylene transfer from S -monofluoromethyl- S -phenyl-2,3,4,5-tetramethylphenylsulfonium tetrafluoroborate ( 2a ) (Figure ) via ylide intermediate as an alternative to freon (CHFX 2 ) chemistry to access monofluorinated cyclopropane , and epoxide derivatives.…”
Section: Introductionmentioning
confidence: 99%